Expression of β‐NGF and high‐affinity NGF receptor (TrKA) in llama (Lama glama) male reproductive tract and spermatozoa - Sari, Luciana María (2018)
β‐Nerve growth factor (β‐NGF) is a seminal plasma element, responsible for inducing ovulation in camelids. The main organ of β‐NGF production remains nondescript. The aims of this study were to (a) characterize gene expression and protein localization of β‐NGF and its main receptor tyrosine kinase receptor A (TrKA) in the llama male reproductive tract, and (b) determine whether the seminal β‐NGF interacts with ejaculated sperm by localizing β‐NGF and TrKA in epididymal, ejaculated, and acrosome‐reacted (AR) sperms and, additionally, by identifying β‐NGF presence in sperm‐adsorbed proteins (SAP). Both β‐NGF and TrkA transcripts are widely expressed along the male reproductive tract, with a higher expression level of β‐NGF at prostate (p < 0.05). β‐NGF immunolabeling was only positive for prostate, whereas TrKA label was present in epithelial and muscular cells of testis, prostate, bulbourethral glands, and epididymis. Using an immunofluorescent technique, β‐NGF was colocalized with TrKA in the middle piece of ejaculated and AR sperm. However, only TrKA was observed in epididymal sperm indicating that β‐NGF could have a seminal origin. This was also confirmed by the identification of four β‐NGF isoforms in SAP. This study extends the knowledge about the participation of β‐NGF/TrkA in llama reproduction, providing evidence that may have roles in the regulation of sperm physiology.